Intensitas Serangan Hama Penggerek Batang Kakao di Perkebunan Rakyat Cipadang, Gedongtataan, Pesawaran - Lestari, Puji; Purnomo, Purnomo (Jurnal Agro Industri Perkebunan, 2018)
Lampung is one of the Province that potential to cacao produce. Stem borer Zeuzera coffeae (Lepidoptera: Cossidae) is one of the pests that often be found, besides Conopomorpha cramerella and Helopelthis sp. Z. coffeae can bore branches and stems it caused xylem damage, plant break easily or plant growth inhibited. The research were conducted from September to October 2017. Sampling was doing at smallholder cocoa plantation in Cipadang Village, Gedongtataan Sub-district, Pesawaran District. Survey was doing to observe pest attacks characteristic, inventory of attacked host, identification of symptoms, and number of fruits. Attack intensity in young plant is higher than in older plants. In 4 years plants the intensity of attack and damage are 11,34% and 7,73%. While the intensity of attack and damage in the 9 plant years are 7,50% and 5,00%.   Keywords: attack intensity, cocoa, stem borer, Zeuzera sp.